The Holmium Laser Enucleation Versus Transurethral Resection in Patients with Benign Prostatic Hyperplasia - Suo, Liu; Sonomjamts, Munkhbayarlakh; Orgoi, Sergelen; Avirmed, Shiirevnyamba (Central Asian Journal of Medical Sciences, 2017)
Objectives: To evaluate efficacy and safety of the holmium laser enucleation of the prostate (HoLEP) compared to transurethral resection of the prostate (TURP) for treatment of benign prostatic hyperplasia. Methods: A total of 62 patients with benign prostatic hyperplasia were included in the study. 42 patients in the TURP group and 18 in the HoLEP group were surgically operated. Preoperative assessments included; international prostate symptom score (IPSS), urinary peak flow rate, prostate volume and serum PSA. Perioperative parameters included; operating time, catheterization time, bladder irrigation, resected tissue weight, perioperative complications, blood transfusion and duration of hospital stays. Results: HoLEP had a statistically longer operating time (p<0.008) with fewer perioperative complications (p<0.0001) and shorter irrigation time (p=0.0001) than TURP. Moreover, significantly more prostatic tissue was removed by HoLEP (p<0.0001) than TURP. There were no statistical differences in catheterization time, blood transfusion and duration of hospital stay days. Conclusion: HoLEP is a safe and effective procedure for surgical treatment of prostatic benign hyperplasia.